NOACs - Nichols, Emma Hitt (MD Conference Express, 2015)
There are now 4 novel oral anticoagulants available as an alternative to vitamin K antagonists for the risk reduction of stroke and systemic embolism in patients with nonvalvular atrial fibrillation. However, many unanswered questions remain about their use in clinical practice, and numerous trials are ongoing.